Can Vocational Education Improve Schooling and Labour Outcomes? Evidence from a Large Expansion - Jo\~ao R. Ferreira; Pedro S. Martins (Institute of Labor Economics (IZA), 2023)
We evaluate the education and labour impact of vocational education and training (VET). Identification draws on different IVs from the large-scale, staggered introduction of VET courses in public schools in Portugal from 2005. We also exploit the large gender differences in VET, with many courses selected almost only by either boys or girls. Drawing on rich student-school matched panel data, we find that VET increased upper-secondary graduation rates dramatically: our LATE estimates typically exceed 50 percentage points. These effects are even stronger for low-achieving students and welfare recipients. Moreover, we find evidence of regional youth employment growth following VET expansions. VET graduates also benefit from higher wages and other positive outcomes over several years, compared to both academic-track and lower-secondary graduates.
Keywords: I21; I26; I28; J24; 330; educational attainment; vocational education; matched student-teacher-school data; VET wage differentials